Consumers Perception of Organic and Ecological Vegetables in Porto-Novo City, South-Benin - Assogba, S. Claude-Gervais; Lègba, H. Théodora; Aïssoun, S. Murelle (European Journal of Applied Sciences, 2022)
Vegetables production and consumption play an important role in achieving the food and nutrition security objectives and fight against unemployment and in achieving the objectives of food and nutrition security. In order to intensify organic and ecological vegetable production and consumption in Benin’s cities a study of the consumers’ perception of these vegetables was conducted in Porto-Novo, second biggest city of Benin after Cotonou. The study aims at determining factors which underline people’s decisions to consume organic and ecological vegetables and the importance of economic, environmental and social factors as perceived by actors. Data used were collected from a sample of 130 consumers encountered at the organic and ecological vegetable production and consumption sites, by using questionnaires with kobo collect application. Likert scale based on items formulated from sustainable vegetable concepts, was used as the basis for data collection and analysis. Statistic parameters were used to analyse data. The study shows that organic and ecological vegetables consumers belong to various socio- professional categories with a monthly income less than 100,000 FCFA for nearly 60% of consumers. Vegetables are consumed every day by nearly 46% of respondents who devote weekly to them, nearly 2,700 ( 2,019.828) FCFA. Consumers perceive organic and ecological vegetables as contributing to the reduction of food poisoning, the creation of employment and entrepreneurship opportunities for young people and to the environment protection. They facilitate digestion, improve human health and strengthen the immune system. Unfortunately, according to consumers, organic and ecological vegetables are not well promoted and therefore poorly known in Porto-Novo. So promotion actions need to be taken to facilitate vegetable consumption at a large scale.